2012
DOI: 10.26719/2012.18.4.337
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice regarding breast cancer and breast self-examination among a sample of the educated population in Iraq

Abstract: This cross-sectional, questionnaire-based study evaluated the knowledge, attitude and practice towards breast cancer and breast self-examination (BSE) among 387 (302 females and 85 males) educated Iraqis affiliated to 2 Iraqi universities. The participants were categorized into 3 occupations: student (71.3%), teaching staff (10.3%) and administrative staff (18.3%). About half of the participants had a low knowledge score (< 50%); only 14.3% were graded as "Good" and above. Almost 75% of the participants believ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
83
8
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(116 citation statements)
references
References 20 publications
23
83
8
2
Order By: Relevance
“…Changes in the distribution patterns of the stage at diagnosis are important indicators of the success of the awareness campaigns and the effectiveness of any screening program. Earlier studies highlighted the gaps in the knowledge, attitudes and practices among Iraqi women regarding breast cancer [20][21][22][23][24]; and consequently paved the way towards promoting the adoption of a comprehensive national breast cancer control strategy based upon public education campaigns, and early detection and treatment protocol guidelines [6,[10][11][12]25].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the distribution patterns of the stage at diagnosis are important indicators of the success of the awareness campaigns and the effectiveness of any screening program. Earlier studies highlighted the gaps in the knowledge, attitudes and practices among Iraqi women regarding breast cancer [20][21][22][23][24]; and consequently paved the way towards promoting the adoption of a comprehensive national breast cancer control strategy based upon public education campaigns, and early detection and treatment protocol guidelines [6,[10][11][12]25].…”
Section: Discussionmentioning
confidence: 99%
“…5 In our study, be scared 71.5%, see a doctor 88.2%, go to prayer 80.5%, traditional medicine 44.3%, agree to do mastectomy 54.7%, time to see doctor (57.5%) within 1 week when Compared to other study, be scare 47.5%, see a doctor 88.2%, go to prayer 27.9%, traditional medicine 1%, agree to do mastectomy 89.7%, time to see doctor (92.2%) within 1 month. 7 Also, other study done in Iran, found that 94.7% will consult a doctor, 2.4% will do nothing.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 16.4% who were not interested in teaching BSE, lacking time was the main reason particularly among students 45.5%. 5 Interest in doing BSE has been reported in other regional studies such as in United Arab Emirates where 90% of nurses had a positive attitude to provide knowledge on the risk factors of breast cancer and about 83% reported that they had taught BSE to others. 6 A study done among schoolteachers in Lagos, Nigeria showed that participants had positive attitude towards breast cancer as 84% said they will see a doctor if they discover a breast lump, followed by 62% will go to prayer house and 50% will be scared.…”
mentioning
confidence: 99%
“…A study in Saudi Arabia in 2009to assess knowledge about breast cancer among female students showed limited knowledge about breast cancer among high school and college female students, however, the students were very enthusiastic to learn about breast cancer and itsprevention 15 . Iraq study in 2012 found that, about half of the participants had a low knowledge score (< 50%); only 14.3% were graded as "Good" and above 16 . In Gaza, efforts to improve early detection of breast cancer should also be directed at learning and understanding the barriers to breast cancer screening, empowering women to seek health care, and providing infrastructure for appropriate screening, diagnosis and treatment 17 .…”
Section: Discussionmentioning
confidence: 99%